2022
DOI: 10.3389/fpsyg.2022.1021904
|View full text |Cite
|
Sign up to set email alerts
|

Developments in early adolescents’ self-regulation: The importance of teachers’ supportive vs. undermining behavior

Abstract: Research has established that the ability to self-regulate is an important factor in adolescents’ learning, and cognitive and social functioning. Several theories on self-regulation and classroom studies suggest effects of the social learning environment on students’ self-regulation. However, most studies investigating these relations have a cross-sectional correlational design and do not relate to adolescents, resulting in little knowledge about causal directions and adolescents. This study extends existing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 121 publications
(271 reference statements)
0
1
0
2
Order By: Relevance
“…Guru yang memiliki pemahaman yang baik tentang pembelajaran regulasi diri dan menganggapnya penting dalam proses pembelajaran cenderung lebih fokus pada pengembangan keterampilan regulasi diri siswa dan memberikan dukungan yang tepat dalam mencapai tujuan belajar mereka. Perkembangan regulasi diri siswa dalam belajar juga terbukti berkaitan positif dengan aspek-aspek dukungan guru yang diberikan yaitu dukungan otonomi, penyediaan struktur, dan keterlibatan guru dalam pembelajaran siswa (Opdenakker, 2022). Dalam penelitian ini, Opdenakker mengukur perkembangan regulasi diri siswa dalam belajar https://doi.org/10.24912/ jmishumsen.v7i3.26764 secara longitudinal melalui masa transisi dari pendidikan dasar ke pendidikan menengah dan selama beberapa bulan di awal tahun pertama mereka di pendidikan menengah.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Guru yang memiliki pemahaman yang baik tentang pembelajaran regulasi diri dan menganggapnya penting dalam proses pembelajaran cenderung lebih fokus pada pengembangan keterampilan regulasi diri siswa dan memberikan dukungan yang tepat dalam mencapai tujuan belajar mereka. Perkembangan regulasi diri siswa dalam belajar juga terbukti berkaitan positif dengan aspek-aspek dukungan guru yang diberikan yaitu dukungan otonomi, penyediaan struktur, dan keterlibatan guru dalam pembelajaran siswa (Opdenakker, 2022). Dalam penelitian ini, Opdenakker mengukur perkembangan regulasi diri siswa dalam belajar https://doi.org/10.24912/ jmishumsen.v7i3.26764 secara longitudinal melalui masa transisi dari pendidikan dasar ke pendidikan menengah dan selama beberapa bulan di awal tahun pertama mereka di pendidikan menengah.…”
Section: Pendahuluanunclassified
“…Selain itu, hasil penelitian lainnya juga menjelaskan bagaimana dukungan sosial (dari guru, orang tua, dan rekan sebaya) bersama dengan modal psikologis menjadi sumber daya sosial dan pribadi yang penting bagi siswa sekolah dasar untuk meningkatkan keterlibatan dalam belajar dan pemecahan masalah yang berfokus pada solusi, yang pada gilirannya dapat meningkatkan kesejahteraan mereka. Tak hanya itu, secara khusus dukungan sosial dari guru juga terbukti berhubungan dengan regulasi diri siswa dilihat dari sudut pandang guru (Thomas, et al, 2022) dan sudut pandang siswa (Opdenakker, 2022).…”
Section: Pendahuluanunclassified
“… Stroet et al (2013) found that students’ perceptions of supportive teaching positively correlate with their overall performance in learning-related tasks. However, in studies focusing on teacher perceptions of support, this correlation is typically weak or nonexistent ( Deci, 1975 ; Entwistle, 1991 ; Skinner and Belmont, 1993 ; Opdenakker, 2022 ). This discrepancy suggests that the impact on students may be more about their perception of teacher behavior than the behavior itself.…”
Section: Introductionmentioning
confidence: 99%